Keragaman Sifat Kuantitatif dan Kualitatif Ayam Kampung di Kota Kupang dan Kabupaten Kupang, Nusa Tenggara Timur: The Variability of Quantitative and Qualitative Traits of Kampong Chicken in Kupang City and Kupang Regency, East Nusa Tenggara - Ni Made Paramita Setyani; Diana Meliani Sabat (Jurnal Peternakan Lahan Kering, 2023)
The aim of this study was to analyze the variability of quantitative and qualitative traits of kampong chickens in Kupang City and Kupang Regency. A total of 140 chickens consisting of 66 male kampong chickens and 74 female kampong chickens were used in this study. The method used was a direct observation survey on the quantitative and qualitative traits of kampong chickens. The association between sexes and quantitative traits was analyzed by t-test, while the qualitative data was analyzed by counting for the percentage. The diversity was determined by calculating the coefficient of variation (KK) of quantitative data. The results showed that male kampong chickens in Kupang City and Kupang Regency were dominated by 41.89% black feathered chickens, 37.88% yellow beak color, and 39.39% yellow shank color. Meanwhile, female kampong chickens were 43.94% red feathered, 53.05% black beak, and 50.00% black shanks. Black mottled feathers were found in male kampong chickens, whereas not found in female kampong chickens. Based on the quantitative characteristics, the wing length, tibia length, shank length, and the third finger length male kampong chicken were significantly higher than female kampong chicken (P≤0.05), while the shank circumference was not significantly different (P≥0.05). It can be concluded that kampong chickens in Kupang City and Kupang Regency was diverse based on quantitative traits.